Preparation method of long-acting interface lubricating coating

By modifying nanosol and microporous powder, loading silicone oil and building a dense interfacial lubricating coating, the existing coating has solved the problems of poor wear resistance, low anti-ice effect and insufficient anti-biological adhesion performance, and achieved high efficiency, Long-term lubrication and protective effect.

CN119463591AActive Publication Date: 2025-02-18SOUTHEAST UNIV

Patent Information

Application Number
CN202411574502.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-06
Publication Date
2025-02-18
Estimated Expiration
2044-11-06

AI Technical Summary

Technical Problem

Due to insufficient structural density and long-term lubricity, existing interface lubricating coatings based on silicone oil have problems such as poor wear resistance, low anti-ice effect and insufficient anti-biological adhesion performance.

Method used

Nanosol and microporous powder are used for modification, and the hydrophobization of low-surface energy substances is modified and nanoparticles and silicone oil are loaded in the porous structure. A dense interfacial lubricating organic and inorganic hybrid coating is constructed in combination with spraying or brushing processes.

Benefits of technology

It realizes an interface lubricating coating with dense structure, high oil carrying capacity and slow release of silicone oil, which has good long-term wear resistance, anti-ice and anti-biological adhesion performance, and also has good corrosion resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119463591A_ABST
    Figure CN119463591A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a long-acting interface lubricating coating, which comprises the following steps: (1) adding 5-7 parts by mass of nano sol, 4-6 parts by mass of micron porous powder, 1.0-1.2 parts by mass of low surface energy substance and 4-6 parts by mass of ammonia water into 80-120 parts by mass of ethanol, and stirring under a water bath heating condition to obtain a modified micron particle suspension, the suspension liquid is dried into powder at high temperature, and modified porous powder is obtained; (2) fully mixing 0.8-1.2 parts by mass of the modified porous powder and 3-5 parts by mass of silicone oil, putting the mixture into a vacuum pump to vacuumize so that the silicone oil can enter the modified porous powder, and after the vacuum state is removed, separating redundant silicone oil to obtain porous powder containing silicone oil; (3) carrying out hole sealing treatment on the porous powder containing the silicone oil, drying at a high temperature, and then mixing with the silicone oil to obtain a mixed solution of the hole sealing powder and the silicone oil; and (4) firstly adding 2.5-4 parts by mass of resin into 2-5 parts by mass of a diluent, then adding 0.5-0.6 part by mass of a silane coupling agent, then adding 0.5-0.8 part by mass of the mixed solution obtained in the step (3), finally adding 0.75-1.2 parts by mass of a curing agent, uniformly mixing, brushing or spraying onto a substrate, and airing to obtain the interface lubricating coating.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing a long-acting interface lubricating coating. Background Art

[0002] In nature, pitcher plants, poison dart frogs and other creatures can secrete a lubricating substance on their skin surface to catch prey. Inspired by this, people have developed a porous material injected with lubricant, which plays a lubricating role by injecting lubricating oil into the surface microstructure to achieve the effect of easy cleaning and anti-icing. The lubricant added to this type of lubricating coating reported so far is generally silicone oil, because silicone oil has good chemical stability and good lubricity.

[0003] However, the current silicone oil-based interfacial lubricating coatings have the problems of poor wear resistance, low anti-icing and anti-biological attachment effects due to their insufficient structural density and long-term lubricity (small amount of oil stored in the carrier and fast release). Summary of the invention

[0004] Purpose of the invention: The purpose of the present invention is to provide a method for preparing a long-lasting interface lubricating coating. The interface lubricating coating prepared by this method has a dense structure, a high oil loading capacity and can slowly release the oil, so it has good long-term wear resistance, anti-icing and anti-biological adhesion properties. At the same time, the coating also has good anti-corrosion properties due to the presence of its hydrophobic particles and lubricating layer.

[0005] Technical solution: The method for preparing the long-lasting interface lubricating coating of the present invention comprises the following steps:

[0006] (1) adding 5 to 7 parts by weight of nanosol, 4 to 6 parts by weight of micron porous powder, 1.0 to 1.2 parts by weight of low surface energy material and 4 to 6 parts by weight of ammonia water to 80 to 120 parts by weight of ethanol, stirring under heating conditions in a water bath to obtain a modified micron particle suspension, and drying the suspension at high temperature to obtain a powder to obtain a modified porous powder;

[0007] (2) 0.8-1.2 parts by weight of the modified porous powder and 3-5 parts by weight of silicone oil are fully mixed, and the mixture is placed in a vacuum pump to evacuate the mixture so that the silicone oil can enter the modified porous powder. After the vacuum state is removed, the mixture is allowed to stand, and after the silicone oil and the powder are completely separated, the upper silicone oil is sucked away using a rubber-tipped dropper to obtain a porous powder containing silicone oil;

[0008] (3) sealing the porous powder containing silicone oil, drying it at high temperature and then mixing it with silicone oil to obtain a mixture of sealing powder and silicone oil;

[0009] (4) First add 2.5 to 4 parts by weight of resin into 2 to 5 parts by weight of diluent, then add 0.5 to 0.6 parts by weight of silane coupling agent, then add 0.5 to 0.8 parts by weight of the mixed solution of step (3), and finally add 0.75 to 1.2 parts by weight of curing agent, mix well, brush or spray onto the substrate, and dry to obtain an interface lubricating coating.

[0010] Wherein, in step (1), the nanosol is a silicon dioxide nanosol or a titanium dioxide nanosol; the particle size of the nanosol is 5 to 40 nm; the solid content of the nanosol is 10 wt.% to 35 wt.%, and the pH value is 9 to 12.

[0011] Wherein, in step (1), the micron porous powder is one of ceramic, diatomaceous earth or glass porous microspheres with a particle size of 10 to 50 μm.

[0012] Wherein, in step (1), the low surface energy substance is perfluorodecyltriethoxysilane or perfluorooctyltriethoxysilane.

[0013] Wherein, in step (1), the water bath heating temperature is not less than 50°C.

[0014] Wherein, in step (1), the suspension is placed in an oven at 90-100° C. for 32-36 hours to dry into powder, and then ground and screened using a 200-mesh sieve.

[0015] Wherein, in step (2), the reaction is carried out under vacuum for not less than 24 hours.

[0016] The sealing process referred to in the present invention is as follows: a cationic polymer (at least one of chitosan, polyethyleneimine, polystyrene or polyacrylamine) solution is mixed with a porous powder containing silicone oil in a mass ratio of 1:2, and the cationic polymer is covered on the surface of the porous powder by electrostatic action under mechanical stirring conditions of 300r / 30min, and after centrifugation at 8000r / 3min, the excess cationic polymer is washed with ethanol or water to remove; after the cationic polymer is covered, the surface of the porous powder is positively charged; then an anionic polymer (sodium polystyrene sulfonate, poly A solution of at least one of acrylic acid or polyacrylonitrile) is mixed with a porous powder in a volume ratio of 1:2 (same as above), and an anionic polymer is covered on the surface of the porous powder by electrostatic action under mechanical stirring conditions of 300r / 30min. After centrifugation at 8000r / 3min, excess anionic polymer is washed with ethanol or water to remove it; a composite film layer constructed of a cationic polymer and anionic polymer is obtained on the surface of the porous powder, completing the sealing treatment of the porous powder. The composite film layer has a loose network structure, which can both release the silicone oil and slow down the release rate of the silicone oil.

[0017] Wherein, in step (3), the mixing mass ratio of the sealing powder and the silicone oil is 1:1 to 1.5 to obtain a mixed liquid.

[0018] Wherein, in step (4), the resin is one of fluorocarbon resin, acrylic resin, polyurethane resin or urea-formaldehyde resin.

[0019] Wherein, in step (4), the silane coupling agent is one of KH550, KH560 or KH570.

[0020] The present invention firstly utilizes low surface energy molecules to hydrophobically modify micron porous particles and retain some hydroxyl groups, then loads nanoparticles in the porous structure, subsequently injects silicone oil into the pores, and finally uses a spraying or brushing process to construct a three-dimensional dense interface lubricating organic-inorganic hybrid coating on the surface of a substrate with an epoxy bonding layer. The coating has good anti-icing performance and long-term wear resistance.

[0021] Beneficial effects: Compared with the prior art, the present invention has the following significant effects: the interface lubricating coating prepared by the method of the present invention has a dense structure (ensuring structural strength) and good lubricating performance (small friction resistance and small friction coefficient). The improvement of lubricating performance is because the carrier is slowly released while greatly increasing the load of silicone oil. Therefore, on the basis of high strength and good lubricating performance, the coating has good long-term wear resistance (linear friction with a dust-free cloth under a load of 500g, the round-trip friction length is 20cm, and one round trip is one cycle. After 500 cycles, its mass loss is only 0.4%, and the sliding angle does not change much), anti-icing (relative to the surface of an untreated glass slide, the ice adhesion is reduced by more than 50%) and anti-biological attachment performance (compared with the continuous growth of Chlorella on the original glass slide, there is almost no growth of Chlorella on the interface lubricating coating); the long-lasting interface lubricating coating of the present invention can be used on high-voltage towers, high-voltage cables, glass curtain walls of buildings, wind turbines, solar panels and airplanes. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 is the SEM image of modified diatomite;

[0023] Figure 2 FTIR spectra of diatomite before and after modification;

[0024] Figure 3 is the thermogravimetric analysis curve of the oil-containing porous powder in Example 1;

[0025] Figure 4 is the wetting angle of the modified diatomaceous earth (a) and the contact angle of the interfacial lubricating coating of Example 1 (b);

[0026] Figure 5The self-cleaning effects of different pollutants on the interface lubricating coating of Example 1: (a) cement (b) chocolate sauce (c) artificial feces;

[0027] Figure 6 The contact angle and sliding angle of the interface lubricating coating of Example 1 change with the number of days of immersion (left) and the actual picture of silicone oil floating on the water surface after the coating is immersed for two weeks (right);

[0028] Figure 7 The morphology of the surface of the interface lubricating coating of Example 1 before and after the tape is pressed: (a) before the tape is pressed, (b) after the tape is pressed;

[0029] Figure 8 is the adhesion of ice on the original glass slide and on the glass slide containing the interface lubricating coating of Example 1;

[0030] Fig. 9 The performance change of the interface lubricating coating of Example 1 with temperature; wherein, the left picture shows the change of mass loss of the interface lubricating coating of Example 1 in a 100°C oven with time, and the right picture shows the change of contact angle and sliding angle of the coating of Example 1 with heating time;

[0031] Fig.10 The performance change of the interface lubricating coating of Example 1 with friction; wherein the left picture shows the change of mass loss of the interface lubricating coating of Example 1 with the number of frictions, and the right picture shows the change of contact angle and sliding angle of the coating of Example 1 with the number of frictions;

[0032] Fig.11 This is the electrochemical impedance spectroscopy (EIS) test of the interface lubricating coating of Example 1, the upper figure is the Bode diagram, and the lower figure is the Nyquist diagram;

[0033] Fig.12 The surface morphology of the interface lubricating coating of Example 1 before and after the salt spray corrosion resistance test;

[0034] Fig.13 The performance comparison of the pure resin coating and the interface lubricating coating of Example 1 in preventing the adhesion and growth of Chlorella; from top to bottom, the surface photo of Chlorella after 7 days of immersion culture, the photo after 7 days of immersion culture of Chlorella after removing the Chlorella not attached to the coating surface with sterile artificial seawater (ASW), and the fluorescence photo obtained by capturing the adhesion of microalgae on the coating through a fluorescence microscope;

[0035] Fig.14 The SEM morphology of the surface of the interface lubricating coating of Example 1 before (a) and after (b) the wear test by Tabour abrasion instrument under a load of 500 g;

[0036] Fig.15 This is the thermogravimetric analysis curve of the oil-containing porous powder of Example 2;

[0037] Fig.16 The topography of the surface of the interfacial lubricating coating of Example 2 after being drawn by the tape;

[0038] Fig.17 is the adhesion of ice on the original glass slide and on the glass slide containing the interface lubricating coating of Example 2;

[0039] Fig.18 The performance change of the interface lubricating coating of Example 2 with temperature; wherein, the left picture shows the change of mass loss of the interface lubricating coating of Example 2 in a 100°C oven with time, and the right picture shows the change of contact angle and sliding angle of the coating of Example 2 with heating time;

[0040] Fig.19 The performance change of the interface lubricating coating of Example 2 with friction; wherein the left picture shows the change of mass loss of the interface lubricating coating of Example 2 with the number of frictions, and the right picture shows the change of contact angle and sliding angle of the coating of Example 2 with the number of frictions;

[0041] Fig. 20 This is a morphology of the surface of the interfacial lubricating coating of Example 3 after being drawn by the tape;

[0042] Fig.21 is the adhesion of ice on the original glass slide and on the glass slide containing the interface lubricating coating of Example 3;

[0043] Fig. 22 The performance changes of the interface lubricating coating of Example 3 with temperature; wherein, the left picture shows the change of mass loss of the interface lubricating coating of Example 3 in a 100°C oven with time, and the right picture shows the change of contact angle and sliding angle of the coating of Example 3 with heating time;

[0044] Fig.23 The performance change of the interface lubricating coating of Example 3 with friction; the left picture shows the change of mass loss of the interface lubricating coating of Example 3 with the number of frictions, and the right picture shows the change of contact angle and sliding angle of the coating of Example 3 with the number of frictions;

[0045] Fig.24 The figures are photos of the coatings formed after the comparative example 1 and the embodiment 1 were mixed with the resin respectively; wherein, the upper figure is a static state of the solution after the particles of the comparative example 1 were mixed with the resin without adding the silane coupling agent, and a surface photo of the prepared coating; the lower figure is a static state of the solution after the particles of the embodiment 1 were mixed with the resin after adding the silane coupling agent, and a surface photo of the prepared coating. DETAILED DESCRIPTION

[0046] Example 1

[0047] The method for preparing the long-acting interface lubricating coating of the present invention comprises the following steps:

[0048] (1) Under the conditions of 50° C. water bath heating and magnetic stirring, 5 parts by mass of silica sol, 0.5 parts by mass of perfluorodecyltriethoxysilane and 4 parts by mass of ammonia water are added to 80 parts by mass of ethanol, and stirred for 3 hours. Then, 4 parts by mass of diatomaceous earth and 0.5 parts by mass of perfluorodecyltriethoxysilane are added to the solution, and stirred for 3 hours to obtain a modified micron particle suspension; the suspension is placed in a 90° C. oven for 36 hours and dried into powder, and after grinding, it is passed through a 200-mesh sieve to obtain a modified porous powder;

[0049] (2) 0.8 parts by weight of the modified porous powder of step (1) was fully mixed with 3 parts by weight of silicone oil, and then placed in a vacuum pump to evacuate the porous powder so that the silicone oil could enter the porous powder. After 24 hours under vacuum, the mixture was allowed to stand, and after the silicone oil and the powder were completely separated, the upper silicone oil was sucked away using a rubber-tipped dropper to obtain a porous powder containing silicone oil;

[0050] (3) performing pore sealing treatment on the porous powder containing silicone oil, drying it in an oven at 100° C., and then mixing it with silicone oil in a mass ratio of 1:1 to obtain a mixture of pore sealing powder and silicone oil;

[0051] (4) First add 2.5 parts by mass of resin to 2 parts by mass of butyl acetate, then add 0.5 parts by mass of silane coupling agent, then add 0.5 parts by mass of the mixed solution of step (3), and finally add 0.75 parts by mass of isocyanate curing agent. After mixing, brush or spray it onto the substrate, and dry it at room temperature for 24 hours to obtain an interface lubricating coating.

[0052] Figure 1 This is the SEM image of the modified diatomaceous earth in step (1). It can be seen from the figure that there are many agglomerated particle structures in the pores of the diatomaceous earth. These agglomerates are the modified SiO2 particles. This morphology shows that the diatomaceous earth has successfully loaded the hydrophobic SiO2 particles, and its pore structure is filled with the hydrophobic SiO2 particles. Such a structure can ensure that the silicone oil will not be easily released after being injected into the pores of the diatomaceous earth particles, thereby ensuring the long-term effectiveness of the coating.

[0053] Figure 2 FTIR spectra of diatomite before and after modification in step (1). It can be seen from the figure that the diatomite after modification has a wavelength of 3400 cm -1 The nearby -OH groups have a reduced transmittance after modification but still exist, and the modified diatomite has a -1 The appearance of the CF peak nearby indicates the success of the modification. Due to the presence of the -OH group, the modified diatomaceous earth particles can participate in the subsequent curing process of the resin, complete the bonding with the resin, solve the compatibility problem between the resin and the powder particles, and thus enhance the strength and wear resistance of the coating.

[0054] Figure 3 This is the thermogravimetric analysis curve of the oil-containing porous powder in step (2). It can be seen from the figure that the heat loss of the particles before and after heating is 57%, which is basically the loss of silicone oil, that is, the oil absorption rate of the particles is about 57%. The particles have good silicone oil loading performance due to the natural porous structure of diatomaceous earth and the rough structure of hydrophobic SiO2, thereby ensuring that the prepared coating has a good long-term lubricating effect.

[0055] Figure 4 (a) is the wetting angle of modified diatomaceous earth. It can be seen that the hydrophobicity of the modified diatomaceous earth is very good. Its contact angle is greater than 150° and the rolling angle is less than 1°. It has super hydrophobic properties, and water droplets will be adsorbed on the needle tube, showing extremely low adhesion between the water droplets and the surface. Figure 4 (b) is the wetting angle of the interfacial lubricating coating of Example 1. It can be seen that the contact angle of the coating is 107.4°, and the water droplets on its surface are hemispherical, which is caused by the dimethyl silicone oil covering the coating surface. However, its sliding angle is as low as 17.3°, showing good lubrication performance.

[0056] Figure 5 The self-cleaning effects of different pollutants on the coating are as follows: (a) cement (b) chocolate sauce (c) artificial feces. It can be seen that the coating in this example has a good self-cleaning effect regardless of whether it is a low-viscosity or high-viscosity substance, or a substance with water as a solvent or a substance with other substances such as oil as a solvent. Its cleaning function is not limited to aqueous solutions.

[0057] Figure 6 The contact angle and sliding angle of the interface lubrication coating change with the number of days of immersion (left) and the actual picture of silicone oil floating on the water surface after the coating is immersed for two weeks (right). It can be seen from the figure that the contact angle and sliding angle of the coating have not changed significantly within 11 days, indicating that the coating has a certain long-term performance in water. In addition, it can be seen from the right picture that a shallow layer of silicone oil can be observed on the surface of the water, indicating that the silicone oil in the coating is continuously released to the outside to continuously maintain the self-cleaning performance of the surface.

[0058] The coating was qualitatively tested using the cross-hatch method. The specific method is to use a cross-hatch tool to scratch the coating surface. Figure 7 The grids shown are all 1mm×1mm squares. Then tape is stuck on the top of the grid, and a weight of 1kg is rolled on the tape to apply pressure. After pressing for 1 minute, the tape is torn off the surface of the coating with the grid, and the shedding of the grid is observed. The adhesion level of the coating is judged according to the test standard of the cross-cut tape adhesion test. Figure 7(a) is a morphology of the surface of the interfacial lubrication coating after the tape is pressed: (a) before the tape is pressed, (b) after the tape is pressed. It can be seen that the grid has not fallen off at all. According to the test standard, the adhesion level of the coating is qualitatively judged to be level 0. The coating of Example 1 has better substrate adhesion.

[0059] The ice adhesion of the coating in Example 1 was compared. Figure 8 is the adhesion of ice on the original glass slide and on the coating of Example 1. From the data results, it can be seen that the ice adhesion of the original glass slide without any treatment is as high as 59.1 kPa, while the ice adhesion on the super-lubricating coating is only 23.8 kPa, and the anti-icing effect is improved by more than 50%, showing good anti-icing performance.

[0060] Fig. 9 The left figure shows the change of mass loss of the interface lubrication coating in a 100°C oven over time. It can be seen that the coating has good heat resistance. The coating is heated in a 100°C oven for nine days and its mass loss is only 1.7%. The right figure shows the change of the contact angle and sliding angle of the coating with heating time. It can be seen that the contact angle and sliding angle of the coating change little within a week, and both have a relatively stable lubrication effect.

[0061] Fig.10 The left picture shows the mass loss of the interface lubrication coating as the number of frictions increases. It can be seen that the coating has good wear resistance. Using a friction tester, the coating is rubbed 500 times with a dust-free cloth under a load of 500g, and its mass loss is only 0.4%. The right picture shows the contact angle and sliding angle of the coating as the number of frictions increases. It can be seen that after 400 frictions, the contact angle and sliding angle of the coating change little, and it can still maintain a stable lubrication effect.

[0062] Fig.11 The impedance analysis diagram of the interfacial lubricating coating is shown in Figure 6. The electrochemical workstation Reference 600 produced by Gamary Company of the United States is used to perform electrochemical impedance spectroscopy (EIS) tests on Q345B substrates, pure resin samples, and SLIPS samples at room temperature. A three-electrode system is used, with a saturated calomel electrode as the reference electrode (SCE), the test sample as the working electrode, and a platinum electrode as the auxiliary electrode. Simulated seawater (3.5% NaCl aqueous solution by mass) is the corrosive medium used in the electrochemical test. The electrochemical impedance spectroscopy uses a sine wave as the excitation signal, with an amplitude (loaded AC disturbance voltage) of 10mV and a scanning frequency range of 100kHz to 10mHz. Before the test, the samples were immersed in a 3.5% NaCl aqueous solution for 1 hour. The large impedance indicates that the coating of Example 1 has good corrosion resistance.

[0063] Fig.12The surface morphology of the interface lubrication coating before and after the salt spray corrosion test. GB / T10125-2021 "Color Artificial Atmosphere Corrosion Test-Salt Spray Test" was used to conduct a neutral salt spray test on the prepared samples using a salt spray box. A NaCl solution with a mass fraction of 5wt.% was used, and the pH value was 6.5-7.2. The test environment temperature was set to 35℃±2, and the saturated barrel temperature was set to 47℃. The sample coating surface was facing up and at an angle of 20° to the vertical line. The salt spray deposition of the 80cm2 salt spray collection device was controlled at 1mL / h~3mL / h. Before the test, the sample needs to be sealed with paraffin, and the changes in the coating caused by the salt spray test should be observed regularly, including blistering, rusting, shedding of the coating, and the development of corrosion around scratches. Sample size: 150mm×75mm, thickness (1±0.2)mm. Conditioning before the experiment: Conditioning for at least 16 hours at (23±2)℃ and relative humidity (50±5)%, with air circulation and without direct sunlight exposure, and then put into the test as soon as possible. From the results, no obvious corrosion phenomenon was observed on the surface of the coating after 1500 hours of neutral salt spray corrosion test, showing excellent corrosion resistance. Since the oil-containing porous powder of Example 1 has a high oil content and can be slowly released, the obtained coating has good corrosion resistance.

[0064] Fig.13 The performance of pure resin coating (three figures on the left) and interfacial lubricating coating (three figures on the right) in preventing Chlorella from adhering and growing is compared. Sterile marine microalgae culture medium was added to sterile artificial seawater (ASW), and the resulting culture medium was used to incubate Chlorella. Different coatings of the same area were immersed in culture dishes containing 30mL of Chlorella (5×106cell / mL) and grown for 7 days in a 23℃ light incubator with a 12h light and 12h dark cycle (upper figure). After that, the Chlorella that was not attached to the coating surface was removed with sterile ASW (middle figure), and the microalgae adhesion was captured by fluorescence microscopy (lower figure). The obtained fluorescence images were used to calculate the coverage rate using Image J software. The results showed that after 6 days of culture, the coverage rate of Chlorella on the pure resin surface was 18.3%, and the coverage rate of Chlorella on the SLIPS coating surface was 0.12%, which was significantly lower than that of pure resin, showing excellent anti-Chlorella adhesion performance.

[0065] The coating of Example 1 was subjected to a Tabour wear test under a load of 500 g, and the coating surface before and after wear was characterized by SEM. The comparison results are as follows: Fig.14 It shows that the coating of Example 1 greatly reduces the resistance generated during rolling friction due to the presence of the lubricating layer, so the surface morphology of the coating does not change much before and after wear. The coating of Example 1 has excellent mechanical wear resistance.

[0066] Example 2

[0067] The method for preparing the long-acting interface lubricating coating of the present invention comprises the following steps:

[0068] (1) Under the conditions of 50° C. water bath heating and magnetic stirring, 5 parts by mass of silica sol, 0.5 parts by mass of perfluorodecyltriethoxysilane and 4 parts by mass of ammonia water are added to 80 parts by mass of ethanol, and stirred for 3 hours. Then, 4 parts by mass of diatomaceous earth and 0.5 parts by mass of perfluorodecyltriethoxysilane are added to the solution, and stirred for 3 hours to obtain a modified micron particle suspension; the suspension is placed in a 90° C. oven for 36 hours and dried into powder, and after grinding, it is passed through a 200-mesh sieve to obtain a modified porous powder;

[0069] (2) 0.8 parts by weight of the modified porous powder of step (1) was fully mixed with 3 parts by weight of silicone oil, and then placed in a vacuum pump to evacuate the porous powder so that the silicone oil could enter the porous powder. After 24 hours under vacuum, the mixture was allowed to stand, and after the silicone oil and the powder were completely separated, the upper silicone oil was sucked away using a rubber-tipped dropper to obtain a porous powder containing silicone oil;

[0070] (3) performing pore sealing treatment on the porous powder containing silicone oil, drying it in an oven at 100° C., and then mixing it with silicone oil in a mass ratio of 1:1 to obtain a mixture of pore sealing powder and silicone oil;

[0071] (4) First add 2.5 parts by mass of resin to 2 parts by mass of butyl acetate, then add 0.5 parts by mass of silane coupling agent, then add 0.5 parts by mass of the mixed solution of step (3), and finally add 0.75 parts by mass of isocyanate curing agent. After mixing, brush or spray it onto the substrate, and dry it at room temperature for 24 hours to obtain an interface lubricating coating.

[0072] Thermogravimetric analysis of the oil-containing porous particles of Example 2 showed the following results: Fig.15 As shown, it can be seen that the heat loss of the particles before and after heating is 60%, which is basically the loss of silicone oil, that is, the oil absorption rate of the particles is about 60%, indicating that the present invention can greatly increase the carrier's loading capacity for silicone oil, thereby ensuring that the prepared coating has a good long-term lubrication effect.

[0073] The coating of Example 2 was qualitatively tested by the cross-hatch method. The specific operation method is to use a cross-hatch tool to scratch the coating surface. Figure 7 The grids shown are all 1mm×1mm squares. Then stick tape on the grids, roll a 1kg weight on the tape to apply pressure, press for 1 minute, then tear off the tape from the coating surface with the grids, observe the shedding of the grids, and judge the adhesion level of the coating according to the test standard of the cross-cut tape adhesion test. The results are shown in Fig.16 As shown, the adhesion grade of the coating of Example 2 is still Grade 0, and the coating of Example 2 has good substrate adhesion.

[0074] The ice adhesion of the coating in Example 2 was compared, and the data results are as follows Fig.17 As shown, the ice adhesion of the original glass slide without any treatment is as high as 61.3 kPa, while the ice adhesion on the super-lubricating coating is only 22.5 kPa. The anti-icing effect is improved by more than 50%, showing good anti-icing performance.

[0075] The coating of Example 2 was placed in an oven at 100°C and the mass loss was recorded over time. The results are as follows: Fig.18 As shown, it can be seen that the coating has good heat resistance. The coating is heated in an oven at 100°C for nine days, and its mass loss is only 1.8%; and its contact angle and sliding angle have hardly changed. It can be seen that the contact angle and sliding angle of the coating change little within a week, and both can have a relatively stable lubrication effect.

[0076] The coating of Example 2 was tested for wear resistance by rubbing it 500 times with a dust-free cloth under a load of 500 g using a friction tester. Fig.19 As shown, its mass loss is only 0.4%, and the mass loss tends to be stable after 300 frictions. In addition, the contact angle and sliding angle change slightly, and can still maintain a stable lubrication effect.

[0077] The performance of the pure resin coating and the coating of Example 2 in preventing the adhesion and growth of Chlorella was compared. Sterile marine microalgae culture medium was added to sterile artificial seawater (ASW), and the obtained culture medium was used to incubate Chlorella. Different coatings of the same area were immersed in culture dishes containing 30 mL of Chlorella (5×106cell / mL) and grown for 7 days in a 23°C light incubator with a 12h light and 12h dark cycle. Afterwards, sterile ASW was used to remove the Chlorella that was not attached to the surface of the coating, and the microalgae adhesion was captured by fluorescence microscopy. The obtained fluorescent images were used to calculate the coverage rate using Image J software. The results showed that after 6 days of culture, the coverage rate of Chlorella on the pure resin surface was 18.9%, and the coverage rate of Chlorella on the SLIPS coating surface was 0.09%, which was significantly lower than that of pure resin, showing excellent anti-Chlorella adhesion performance.

[0078] Example 3

[0079] The method for preparing the long-acting interface lubricating coating of the present invention comprises the following steps:

[0080] (1) Under the conditions of 50° C. water bath heating and magnetic stirring, 5 parts by mass of silica sol, 0.5 parts by mass of perfluorodecyltriethoxysilane and 4 parts by mass of ammonia water are added to 80 parts by mass of ethanol, and stirred for 3 hours. Then, 4 parts by mass of diatomaceous earth and 0.5 parts by mass of perfluorodecyltriethoxysilane are added to the solution, and stirred for 3 hours to obtain a modified micron particle suspension; the suspension is placed in a 90° C. oven for 36 hours and dried into powder, and after grinding, it is passed through a 200-mesh sieve to obtain a modified porous powder;

[0081] (2) 0.8 parts by weight of the modified porous powder of step (1) was fully mixed with 3 parts by weight of silicone oil, and then placed in a vacuum pump to evacuate the porous powder so that the silicone oil could enter the porous powder. After 24 hours under vacuum, the mixture was allowed to stand, and after the silicone oil and the powder were completely separated, the upper silicone oil was sucked away using a rubber-tipped dropper to obtain a porous powder containing silicone oil;

[0082] (3) performing pore sealing treatment on the porous powder containing silicone oil, drying it in an oven at 100° C., and then mixing it with silicone oil in a mass ratio of 1:1 to obtain a mixture of pore sealing powder and silicone oil;

[0083] (4) First add 2.5 parts by mass of resin to 2 parts by mass of butyl acetate, then add 0.5 parts by mass of silane coupling agent, then add 0.5 parts by mass of the mixed solution of step (3), and finally add 0.75 parts by mass of isocyanate curing agent. After mixing, brush or spray it onto the substrate, and dry it at room temperature for 24 hours to obtain an interface lubricating coating.

[0084] Thermogravimetric analysis was performed on the oil-containing porous particles of Example 3. The results showed that the heat loss of the particles before and after heating was 55%, which was basically the loss of silicone oil, that is, the oil absorption rate of the particles was about 55%.

[0085] The coating of Example 3 was qualitatively tested by the cross-hatch method. The specific operation method is to use a cross-hatch tool to scratch the coating surface. Figure 7 The grids shown are all 1mm×1mm squares. Then stick tape on the grids, roll a 1kg weight on the tape to apply pressure, press for 1 minute, then tear off the tape from the coating surface with the grids, observe the shedding of the grids, and judge the adhesion level of the coating according to the test standard of the cross-cut tape adhesion test. The results are shown in Fig. 20 It shows that the adhesion grade of the coating of Example 3 is still grade 0.

[0086] The ice adhesion of the coating of Example 3 was compared, and the data results are as follows Fig.21 It shows that the ice adhesion of the original glass slide without any treatment is as high as 58.2kPa, while the ice adhesion on the super-lubricating coating is only 25.3kPa. The anti-icing effect is improved by more than 50%, showing good anti-icing performance.

[0087] The coating of Example 3 was placed in an oven at 100°C and the mass loss was recorded over time. The results are as follows: Fig. 22 As shown, it can be seen that the coating has good heat resistance. The coating is heated in an oven at 100°C for nine days, and its mass loss is only 1.6%; and its contact angle and sliding angle have hardly changed. It can be seen that the contact angle and sliding angle of the coating change little within a week, and both can have a relatively stable lubrication effect.

[0088] The coating of Example 3 was tested for wear resistance by rubbing it 500 times with a dust-free cloth under a load of 500 g using a friction tester. Fig.23 As shown, its mass loss is only 0.4%, and the mass loss tends to be stable after 300 frictions. In addition, the contact angle and sliding angle change slightly, and can still maintain a stable lubrication effect.

[0089] The performance of the pure resin coating and the coating of Example 3 in preventing the adhesion and growth of Chlorella was compared. Sterile marine microalgae culture medium was added to sterile artificial seawater (ASW), and the resulting culture medium was used to incubate Chlorella. Different coatings of the same area were immersed in culture dishes containing 30 mL of Chlorella (5×106cell / mL) and grown for 7 days in a 23°C light incubator with a 12-h light and 12-h dark cycle. Afterwards, sterile ASW was used to remove the Chlorella that was not attached to the surface of the coating, and the microalgae adhesion was captured by fluorescence microscopy. The obtained fluorescent images were used to calculate the coverage using Image J software. The results showed that after 6 days of culture, the coverage of Chlorella on the pure resin surface was 20.3%, and the coverage of Chlorella on the SLIPS coating surface was 0.30%, which was significantly less than that of the pure resin, showing excellent anti-Chlorella adhesion performance.

[0090] Example 4

[0091] The method for preparing the long-acting interface lubricating coating of the present invention comprises the following steps:

[0092] (1) Under the conditions of 50° C. water bath heating and magnetic stirring, 5 parts by mass of silica sol, 0.5 parts by mass of perfluorodecyltriethoxysilane and 4 parts by mass of ammonia water are added to 80 parts by mass of ethanol, and stirred for 3 hours. Then, 4 parts by mass of diatomaceous earth and 0.5 parts by mass of perfluorodecyltriethoxysilane are added to the solution, and stirred for 3 hours to obtain a modified micron particle suspension; the suspension is placed in a 90° C. oven for 36 hours and dried into powder, and after grinding, it is passed through a 200-mesh sieve to obtain a modified porous powder;

[0093] (2) 0.8 parts by weight of the modified porous powder of step (1) is fully mixed with 3 parts by weight of silicone oil, and then placed in a vacuum pump to evacuate the porous powder so that the silicone oil can enter the porous powder. After 24 hours under vacuum, the mixture is allowed to stand, and after the silicone oil and the powder are completely separated, the excess silicone oil is filtered out by vacuum filtration to obtain porous powder particles containing silicone oil;

[0094] (3) performing pore sealing treatment on the porous powder containing silicone oil, drying it in an oven at 100° C., and then mixing it with silicone oil in a mass ratio of 1:1 to obtain a mixture of pore sealing powder and silicone oil;

[0095] (4) First add 2.5 parts by mass of resin to 2 parts by mass of butyl acetate, then add 0.5 parts by mass of silane coupling agent, then add 0.5 parts by mass of the mixed solution of step (3), and finally add 0.75 parts by mass of isocyanate curing agent. After mixing, brush or spray it onto the substrate, and dry it at room temperature for 24 hours to obtain an interface lubricating coating.

[0096] The oil-containing porous powders obtained in Example 4 and Example 1 are weighed to obtain an initial mass m0, and then placed in an oven and heated at 180°C. They are taken out and weighed every 24 hours until their mass does not decrease, and their mass m1 is recorded. The oil absorption rate of the particles is m0-m1 / m0×100%. Table 1 compares the oil absorption rates of the oil-containing particles obtained by the suction filtration method and the static sedimentation method. It can be seen from the table that the oil absorption rate of the oil-containing porous powder obtained in Example 1 is more than twice that of Comparative Example 1, and the high oil absorption rate ensures the lubrication performance of the powder.

[0097] Table 2 shows the contact angle and sliding angle of the interfacial lubricating coating prepared from the oil-containing porous powder obtained by the suction filtration method and the static sedimentation method. It can be seen that the interfacial lubricating coating prepared from the powder obtained by the static sedimentation method used in Example 1 has better lubrication performance, and its sliding angle is only 10.2°.

[0098] The ice adhesion of the coating of Example 4 was tested, and the results showed that the ice adhesion was 35 kPa, which was higher than that of Example 1 and lower than that of the untreated glass slide.

[0099] Table 1

[0100]

[0101] Table 2

[0102]

[0103] Example 5

[0104] The method for preparing the long-acting interface lubricating coating of the present invention comprises the following steps:

[0105] (1) Under the conditions of 50° C. water bath heating and magnetic stirring, 5 parts by mass of silica sol, 0.5 parts by mass of perfluorodecyltriethoxysilane and 4 parts by mass of ammonia water are added to 80 parts by mass of ethanol, and stirred for 3 hours. Then, 4 parts by mass of diatomaceous earth and 0.5 parts by mass of perfluorodecyltriethoxysilane are added to the solution, and stirred for 3 hours to obtain a modified micron particle suspension; the suspension is placed in a 90° C. oven for 36 hours and dried into powder, and after grinding, it is passed through a 200-mesh sieve to obtain a modified porous powder;

[0106] (2) 0.8 parts by weight of the modified porous powder of step (1) was fully mixed with 3 parts by weight of silicone oil, and then placed in a vacuum pump to evacuate the porous powder so that the silicone oil could enter the porous powder. After 24 hours under vacuum, the mixture was allowed to stand, and after the silicone oil and the powder were completely separated, the upper silicone oil was sucked away using a rubber-tipped dropper to obtain a porous powder containing silicone oil;

[0107] (3) performing pore sealing treatment on the porous powder containing silicone oil, drying it in an oven at 100° C., and then mixing it with silicone oil in a mass ratio of 1:1 to obtain a mixture of pore sealing powder and silicone oil;

[0108] (4) First add 2.5 parts by mass of resin to 2 parts by mass of butyl acetate, then add 0.5 parts by mass of the mixed solution of step (3), and finally add 0.75 parts by mass of isocyanate curing agent, mix well and apply by brushing or spraying on the substrate, and dry at room temperature for 24 hours to obtain an interface lubricating coating.

[0109] Fig.24 The upper figure shows the static state of the solution after the sealing powder and the resin are mixed in Example 5 and the surface photo of the prepared coating; the lower figure shows the static state of the solution after the sealing powder and the resin are mixed in Example 1 and the surface photo of the prepared coating. It can be seen that the particles and the resin in Example 5 are seriously stratified, and the surface of the prepared coating is very rough and uneven, which is caused by the poor compatibility between the particles and the resin, while the particles in Example 1 are well combined with the resin, the particles can be evenly dispersed in the resin, and the prepared coating is also very uniform and smooth.

[0110] The reason why the compatibility between the resin and the particles in Example 5 is very poor is that no silane coupling agent is added or the amount added is too small. The silane coupling agent in the resin before adding the particles can be used to graft amino groups onto the resin, and this group can better combine with the modified oil-containing porous powder, thereby ensuring good compatibility between the particles and the resin.

[0111] Since the coating surface of Example 5 was too rough, its contact angle, ice adhesion and other properties were not further tested.

[0112] Comparative Example 1

[0113] According to patent number CN202011216363.0, this example uses modified silica nano solution to prepare a long-lasting anti-icing coating. The following steps are included:

[0114] (1) Preparation of modified porous silica powder: ethanol, deionized water, and ammonia water were mixed in a ratio of 20:4:1, and after stirring evenly, 1 vol.% of nano-chain silica sol solution was added dropwise, followed by 0.6 vol.% of TEOS as a crosslinking agent, and then 0.6 vol.% of n-octyltriethoxysilane was added for surface modification. Finally, the beaker was sealed and stirred for 24 hours to obtain a modified nano-SiO2 solution. The solution was transferred into an oven at 120°C, completely dried, and sieved with a 200-mesh sieve to obtain a modified porous powder;

[0115] (2) Preparation of anti-icing coating: 10 g of butyl acetate and 10 g of fluorocarbon resin were mixed to obtain a resin solution, and then the modified porous powder obtained in step (1) was added to the resin solution. After ultrasonic mixing for 1 min, 3.33 g of polyisocyanate was added to the mixed solution as a curing agent, and then stirred to obtain a mixed solution;

[0116] (3) Preparation of long-lasting anti-icing coating: The mixed solution obtained in step (2) is spin-coated on the surface of a glass substrate, and then placed in an oven at 80° C. for curing for 2 h to obtain an anti-icing coating.

[0117] The substrate adhesion of the coatings in Example 1 and Comparative Example 1 was compared. The coatings were qualitatively tested using the cross-hatch method. The specific operation method was to use a cross-hatch tool to scratch the coating surface. Figure 7 The grids shown are all 1mm×1mm squares. Then tape is stuck on the top of the grid, and a weight of 1kg is rolled on the tape to apply pressure. After pressing for 1 minute, the tape is torn off the surface of the coating with the grid, and the shedding of the grid is observed. The adhesion level of the coating is judged according to the test standard of the cross-cut tape adhesion test. Figure 7 (a) is a morphology of the surface of the interfacial lubrication coating after the tape is pressed: (a) before the tape is pressed, (b) after the tape is pressed. It can be seen that the grid has not fallen off at all. According to the test standard, the adhesion level of the coating is qualitatively judged to be level 0, while the results of comparative example 1 show that the paint film adhesion is level 1. The coating of Example 1 has better substrate adhesion.

[0118] The ice adhesion of Example 1 and Comparative Example 1 was compared. The ice adhesion on the surface of the coating of Example 1 was only 23.8 kPa, and the anti-icing effect was improved by more than 50%, showing good anti-icing performance. The initial ice adhesion on the surface of the coating of Comparative Example 1 was 58 kPa.

Claims

1. A method for preparing a long-lasting interface lubricating coating, characterized in that: The steps include: (1) adding 5 to 7 parts by weight of nanosol, 4 to 6 parts by weight of micron porous powder, 1.0 to 1.2 parts by weight of low surface energy material and 4 to 6 parts by weight of ammonia water to 80 to 120 parts by weight of ethanol, stirring under heating conditions in a water bath to obtain a modified micron particle suspension, and drying the suspension at high temperature to obtain a powder to obtain a modified porous powder; (2) 0.8-1.2 parts by weight of the modified porous powder and 3-5 parts by weight of silicone oil are fully mixed, and the mixture is placed in a vacuum pump to evacuate the mixture so that the silicone oil can enter the modified porous powder. After the vacuum state is removed, the excess silicone oil is separated to obtain a porous powder containing silicone oil; (3) sealing the porous powder containing silicone oil, drying it at high temperature and then mixing it with silicone oil to obtain a mixture of sealing powder and silicone oil; (4) First add 2.5 to 4 parts by weight of resin into 2 to 5 parts by weight of diluent, then add 0.5 to 0.6 parts by weight of silane coupling agent, then add 0.5 to 0.8 parts by weight of the mixed solution of step (3), and finally add 0.75 to 1.2 parts by weight of curing agent, mix well, brush or spray onto the substrate, and dry to obtain an interface lubricating coating.

2. The preparation method according to claim 1, characterized in that: In step (1), the nanosol is a silicon dioxide nanosol or a titanium dioxide nanosol; the particle size of the nanosol is 5 to 40 nm; the solid content of the nanosol is 10 wt.% to 35 wt.%, and the pH value is 9 to 12.

3. The preparation method according to claim 1, characterized in that: In step (1), the micron porous powder is one of ceramic, diatomaceous earth or glass porous microspheres with a particle size of 10 to 50 μm.

4. The preparation method according to claim 1, characterized in that: In step (1), the low surface energy substance is perfluorodecyltriethoxysilane or perfluorooctyltriethoxysilane.

5. The preparation method according to claim 1, characterized in that: In step (1), the water bath heating temperature is not less than 50°C.

6. The preparation method according to claim 1, characterized in that: In step (1), the suspension is placed in an oven at 90-100° C. for 32-36 hours to dry into powder, and then ground and sieved using a 150-200 mesh sieve.

7. The preparation method according to claim 1, characterized in that: In step (2), the reaction is carried out under vacuum for not less than 24 hours.

8. The preparation method according to claim 1, characterized in that: In step (3), the mixing mass ratio of the sealing powder to the silicone oil is 1:1 to 1.5 to obtain a mixed liquid.

9. The preparation method according to claim 1, characterized in that: In step (4), the resin is one of fluorocarbon resin, acrylic resin, polyurethane resin or urea-formaldehyde resin.

10. The preparation method according to claim 1, characterized in that: In step (4), the silane coupling agent is one of silane coupling agent KH550, silane coupling agent KH560 or silane coupling agent KH570.

Citation Information

Patent Citations

  • A long-lasting anti-icing coating, its preparation method and application

    CN112341873B

  • Lyophobic and oleophylic micro nano-coatings applied to of oil filtering dehydration and preparation method thereof

    CN101601940A

  • Porous powder loaded with super-hydrophobic particles as well as preparation method and application of porous powder

    CN113604095A

  • Super-hydrophobic unit cell powder, preparation method and application of super-hydrophobic unit cell powder in preparation of composite anticorrosive coating

    CN118516003A

Cited By

  • Silicone oil slow-release antifouling coating as well as preparation method and application thereof

    CN121555069A

  • Polyvinyl chloride insulating material for super-scratch-resistant cable and preparation process of polyvinyl chloride insulating material

    CN122302450A